Analysis of Gas Content and Permeability Change Pattern of a Coal Reservoir in the Tectonic Positions Based on a THM Coupled Model. (23rd February 2021) - Ye, Zhenni; Hou, Enke; Li, Huantong; Duan, Zhonghui; Wu, Fan
Abstract : The theory of coalbed methane distribution controlled by tectonism is a hot issue in the field of geofluid-geotectonic interaction research. Taking the geological structure in the scale range of the 1302 working face of a Guojiahe wellfield in a Yonglong mining area as the background, this paper focuses on the basic research problem of the influence of geological structure on the control of coal reservoir gas content and uses a THM coupling model to analyze the change of coalbed gas content and distribution characteristics of different tectonic positions. The change of CBM content and permeability in the anticline, syncline, and faults is analyzed. Accordingly, the variation distance of gas content and reservoir permeability controlled by tectonism of different geological structures is quantified to provide guidance for the selection of CBM-favorable areas. The research results show that the gentle dip syncline hinge zone is a potential gas-rich area with heat preservation and low permeability, while the gentle dip anticline hinge zone is a gas-poor area with low temperature and low pressure and high permeability. The thick coal seam zone of the syncline hinge zone is the potential gas accumulation zone, and the high-permeability area is near the fault plane of a normal fault. The coal matrix near the normal fault is subjected to tensile tectonic stresses to form tensional fissures, and the coal seam in the fault plane area is susceptible to coalbed gas dispersion and increases the permeability of the coal reservoir. The variation distance of gas content and reservoir permeability controlled by the normal fault within the Guojiahe wellfield is 37 m and 54 m from the fault plane, respectively.